2011
DOI: 10.1155/2011/745487
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence of Local Binary Patterns Features for Frontal Face Detection in Surveillance Applications

Abstract: Face detection in video sequence is becoming popular in surveillance applications. The tradeoff between obtaining discriminative features to achieve accurate detection versus computational overhead of extracting these features, which affects the classification speed, is a persistent problem. This paper proposes to use multiple instances of rotational Local Binary Patterns (LBP) of pixels as features instead of using the histogram bins of the LBP of pixels. The multiple features are selected using the sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
(115 reference statements)
0
12
0
Order By: Relevance
“…. , no of samples} and its class label Y n ∈ {1, -1} is used to find weak classifiers h j (x) [31]. These weak classifiers h j (x) are used to construct a strong classifier H(X).…”
Section: The Proposed Methods Video Based Face Recognizationmentioning
confidence: 99%
“…. , no of samples} and its class label Y n ∈ {1, -1} is used to find weak classifiers h j (x) [31]. These weak classifiers h j (x) are used to construct a strong classifier H(X).…”
Section: The Proposed Methods Video Based Face Recognizationmentioning
confidence: 99%
“…Video detecting category addresses issues regarding to automatic detection of anomalous, forbidden, dangerous events or abandoned object (counting moving people, ship detection, after-the-fact event, intruder detection, trajectory-based unusual behavior detection, motion detection, mult iple moving object detection, face detection, pedestrian detection, vehicle detection, unattended object detection, etc) . Video encoding [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [16], [104] [105], [106], [107], [108], [109], [110], [7], [111] [112], [113], [114], [115] [116],[8], [117] Object detection is performed by co mmon statistical learning techniques with dynamically learning background model of the scene and applies the reference model to find out which section of the scene match with mov ing object. Reasoning refers to generating new explanations, facts and knowledge of dynamic scenes by applying inference engine and method (rule and case based reasoning, Bayesian network, decision tree).…”
Section: Communication Layermentioning
confidence: 99%
“…However, due to the lack of spatial relationships among local textures, there have still serious disadvantages in the original LBP representation. Therein, an extension of the LBP called CoLBP [15,16], has been proposed by considering the co-occurrence (spatial context) among adjacent LBPs, which proved promising performances on several classification applications [6]. In addition, by integrating orientation context, Nosaka et al [17,18] explored a rotation invariant co-occurrence among LBP, which is shown to be more discriminant on image classification compared to CoLBP.…”
Section: Introductionmentioning
confidence: 99%